Hybrid Monoterpenoid Indole Alkaloids Obtained as Artifacts from Rauvolfia tetraphylla - Gao, Yuan (Nat Prod Bioprospect, 2015)
ABSTRACT: Five new hybrid monoterpenoid indole alkaloids bearing an unusual 2,2-dimethyl-4-oxopiperidin-6-yl moiety, namely rauvotetraphyllines F–H (1, 3, 4), 17-epi-rauvotetraphylline F (2) and 21-epi-rauvotetraphylline H (5), were isolated from the aerial parts of Rauvolfia tetraphylla. Their structures were established by extensive spectroscopic analysis. The new alkaloids were evaluated for their cytotoxicity in vitro against five human cancer cell lines. GRAPHICAL ABSTRACT: [Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13659-015-0074-2) contains supplementary material, which is available to authorized users.